(untitled) (Applied Biological Research, 2016)
Soil analysis for boron is vital as the range between its deficiency and toxicity is quite narrow and its application slightly above the optimum level may prove oxic to plants. In present study, the extractability of various extractants was assessed in relation to the physicochemical properties of soils. Soil sampling was carried out in 30 orchards in district Kulgam, Kashmir. Four extractants widely used to determine plant-available boron from either acidic or alkaline soils were used. The hot-water-soluble boron (HWSB) extraction procedure was used as a benchmark to observe relative variation in available boron in alternate extractants like calcium chloride-mannitol (CaCl2-mannitol), ammonium acetate and diethylene-triaminepenta-acetic acid-sorbitol (DTPA sorbitol). A significant correlation was found for available B among all the extractants tested, the strongest correlation (r = 0.975** at P<0.01) was observed between HWSB and DTPA-sorbitol and hence it may substitute the hot water extraction method for estimating plant-available B.